A Framework for an Electronic Marketing Delivery System Using Drone - Domaka Nuka Nanwin; Williams Daniel Ofor; Uwaguosa Endurance Ekuase (International Journal on Human-Computing Studies, 2021)
The Novel COVID-19 global outbreak has further increased the benefits and importance of business continuity in challenging scenarios like this pandemic. The impact of technology in the marketing system cannot be over emphasized. This project work has explored the use of the unmanned aerial vehicle (UAV) popularly known as drone in an electronic marketing delivery system to improve the delivery services offered by online shops/ e-businesses which encourages speed in the delivery of goods/ items. A model has been created for the implementation of this system. The Geocode and general Google map API has been used to get a marker for the source and destination on the map that tracks the longitude and latitude of the delivery destination delivery location. The development of the system has focused on the development of the software and not the synchronization of the software and the drone. The system has performed well meeting all the demands of the process.